Unprecedented Atmospheric Ammonia Concentrations Detected in the High Arctic From the 2017 Canadian Wildfires. Issue 14 (24th July 2019) - Lutsch, Erik; Strong, Kimberly; Jones, Dylan B. A.; Ortega, Ivan; Hannigan, James W.; Dammers, Enrico; Shephard, Mark W.; Morris, Eleanor; Murphy, Killian; Evans, Mathew J.; Parrington, Mark; Whitburn, Simon; et al.
Abstract: From 17–22 August 2017 simultaneous enhancements of ammonia (NH3 ), carbon monoxide (CO), hydrogen cyanide (HCN), and ethane (C2 H6 ) were detected from ground‐based solar absorption Fourier transform infrared (FTIR) spectroscopic measurements at two high‐Arctic sites: Eureka (80.05°N, 86.42°W) Nunavut, Canada, and Thule (76.53°N, 68.74°W), Greenland. These enhancements were attributed to wildfires in British Columbia and the Northwest Territories of Canada using FLEXPART back‐trajectories and fire locations from Moderate Resolution Imaging Spectroradiometer (MODIS) and found to be the greatest observed enhancements in more than a decade of measurements at Eureka (2006–2017) and Thule (1999–2017). Observations of gas‐phase NH3 from these wildfires illustrate that boreal wildfires may be a considerable episodic source of NH3 in the summertime high Arctic. Comparisons of GEOS‐Chem model simulations using the Global Fire Assimilation System (GFASv1.2) biomass burning emissions to FTIR measurements and Infrared Atmospheric Sounding Interferometer (IASI) measurements showed that the transport of wildfire emissions to the Arctic was underestimated in GEOS‐Chem. However, GEOS‐Chem simulations showed that these wildfires contributed to surface layer NH3 and NH 4 + enhancements of 0.01–0.11 ppbv and 0.05–1.07 ppbv, respectively, over the Canadian Archipelago from 15–23 August 2017. Key Points: The 2017 Canadian wildfires resulted in the largest observed NH3 total column enhancements in the high Arctic from 1999–2017 GEOS‐Chem surface layer NH3 was enhanced by 0.01–0.11 ppbv (14–550%) in the Canadian high Arctic from 15–23 August 2017 due to wildfires Wildfires may be an important episodic source of NH3 in the summertime high Arctic in addition to the persistent seabird colony source